2006
DOI: 10.1080/13576500500233628
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and rightward bias in line bisection

Abstract: This study investigated line bisection in 10 males with schizophrenia and 15 controls. There was an overall leftward bias, consistent with slight right "pseudoneglect", but the schizophrenia group showed more variation with experimental conditions, suggesting impaired interhemispheric transfer. Specifically, the rightward bias was especially marked when the lines were positioned on the right side of the page, when the right hand was used, and when a right to left scan was adopted. The rightward bias was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The earliest study (Mather et al, 1990) reported a significant leftward bisection error for control subjects, and no significant difference between the patient and control groups. A study by Barnett (2006) also found leftward errors for control subjects, but the errors made by patients did not differ significantly from zero. Two studies from the same laboratory Michel et al, 2007) reported bisection errors in control subjects that were not significantly different from zero, and significant leftward errors for patients.…”
Section: Line Bisection In Patients With Schizophreniamentioning
confidence: 98%
“…The earliest study (Mather et al, 1990) reported a significant leftward bisection error for control subjects, and no significant difference between the patient and control groups. A study by Barnett (2006) also found leftward errors for control subjects, but the errors made by patients did not differ significantly from zero. Two studies from the same laboratory Michel et al, 2007) reported bisection errors in control subjects that were not significantly different from zero, and significant leftward errors for patients.…”
Section: Line Bisection In Patients With Schizophreniamentioning
confidence: 98%
“…Thus, dopamine antagonists might have a normalizing or balancing effect, thereby decreasing both positive symptoms (e.g., delusions, hallucinations) as well as right neglect [76,77]. On the other hand, the association between left neglect in PS and overall negative symptomatology was suggested by Barnett [47]. This view was in agreement with the study by Mayer et al [78] who showed that SP with flat affect ("negative symptoms") were characterized by greater right hemisphere deficit than left hemisphere deficit.…”
Section: Rightward Bisection Bias Left Hemineglectmentioning
confidence: 99%
“…Barnett [47] found that individuals with greater overall negative symptomatology made greater rightward deviations in right hemispace. Furthermore, Benson and Park [49] observed that the magnitude of right deviations was strongly related to delusional ideation.…”
Section: Rightward Bisection Bias Left Hemineglectmentioning
confidence: 99%
See 2 more Smart Citations